Anti-tiger-skin-texture, low-shrinkage and low-odor polypropylene composite material and preparation method thereof
By rationally formulating various components in the polypropylene composite, the problems of tiger skin pattern, shrinkage and odor of polypropylene composite during injection molding are solved, and the anti-tiger skin pattern, low shrinkage and low odor characteristics of the material are achieved, and the performance and application value of the material are improved.
Patent Information
- Application Number
- CN202411962586.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polypropylene composite materials are prone to tiger skin texture, shrinkage and odor problems during injection molding, which affects the performance and application of the material.
A method for preparing polypropylene composite material with anti-tiger skin pattern, low shrinkage, and low odor is adopted to form a composite material with excellent properties by reasonably preparing copolymerized polypropylene, high impact block copolymerized polypropylene, elastomer toughening agent, filler, compatible agent, odor neutralizer, anti-scratch additive and stabilizer.
The material's anti-tiger skin pattern, low shrinkage and low odor characteristics are achieved, ensuring the toughness and dimensional stability of the material, while reducing the density and odor level of the material.
Smart Images

Figure BDA0005217549900000071 
Figure BDA0005217549900000072 
Figure BDA0005217549900000081
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a polypropylene composite material. The obtained material has the characteristics of anti-tiger pattern, low shrinkage and low odor, and belongs to the technical field of polymer material processing and modification. Background Art
[0002] At present, with the rapid development of the automobile industry, the design concept of automobile products is gradually developing towards lightweight, thin-walled, low-carbon, environmentally friendly, healthy and comfortable, and low-cost. However, injection molded products have certain injection defects and characteristic defects. On the one hand, warping, shrinkage marks, tiger stripes, and weld marks are prone to occur during the injection molding process. On the other hand, during the processing and production process, it is easily affected by factors such as extrusion temperature and melting temperature, and partial decomposition and degradation will inevitably occur, producing small molecular volatiles, thereby affecting the final odor state of the material and accessories. Therefore, the demand for low-emission polypropylene materials with ultra-high fluidity, ultra-high rigidity or ultra-high toughness is increasing day by day for various OEMs and component manufacturers.
[0003] Tiger stripes are a common appearance defect of composite materials during injection molding. They appear as wavy stripes on the surface of the injection molded part, and the stripes are generally perpendicular to the melt flow direction during injection molding. Visually, they look like the pattern on tiger skin. They are usually reflected in low melt flow rate materials, thin-walled parts, and large parts. The main causes of tiger stripes are: unstable flow of the melt on the mold surface, rubber relaxation theory, and mold expansion phenomenon. The key factor is the rubber phase in the composite material. Therefore, the solution to most tiger stripes is to increase the melt flow rate of the material, reduce the use of rubber phase elastomers, and lose the toughness and size of the material. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a tiger-skin-resistant, low-shrinkage, low-odor polypropylene composite material. The obtained material can be used for thin-walled automotive interior trims, has excellent tiger-skin-resistant properties, dimensional stability, high fluidity, high toughness, low odor and other properties.
[0005] Another object of the present invention is to provide a method for preparing the polypropylene composite material.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention discloses a polypropylene composite material with anti-tiger pattern, low shrinkage and low odor, which is composed of the following raw materials in percentage by weight: copolymerized polypropylene: 30-60%; high-impact block copolymerized polypropylene: 0-30%; elastomer toughening agent: 0-20%; filler: 15-25%; compatibilizer: 0-3%; odor neutralizer: 0-3%; anti-scratch additive: 0.2-2%; stabilizer: 0.1-2%; and other additives: 0-5%.
[0008] The melt flow rate of the copolymer polypropylene is 30-100 g / 10 min, and it has an anti-tiger pattern effect; the melt flow rate of the high-impact block copolymer polypropylene is 10-50 g / 10 min.
[0009] The elastomer toughening agent is ethylene-octene copolymer or styrene-ethylene-butadiene-styrene block copolymer or a combination of the two, with a density of 0.88-0.91 g / cm3 and a melt flow rate of 1-15 g / 10 min.
[0010] The filler is one or more of talcum powder, whisker, basalt fiber, glass fiber and carbon fiber.
[0011] The compatibilizer is maleic anhydride grafted polypropylene, the effective grafting activity is above 5%, and the melt index is 5-20g / 10min.
[0012] The odor neutralizer is one or more of a plastic deodorizer, an adsorbent, a natural zeolite, and an extractant.
[0013] The anti-scratch additive is one or a combination of amide additives or silicone additives.
[0014] The stabilizer is a primary antioxidant and a secondary antioxidant that are considered necessary by those skilled in the art, wherein the primary antioxidant is a hindered phenol or thioester antioxidant, and the secondary antioxidant is a phosphite or lipid antioxidant.
[0015] The other additives are one or a combination of anti-light additives, flame retardants, antistatic additives, surfactants, plasticizers, and antimicrobial additives that are considered necessary by those skilled in the art.
[0016] The preparation method of the above-mentioned anti-tiger pattern, low shrinkage, low odor polypropylene composite material comprises the following specific steps:
[0017] (1) Weigh copolymer polypropylene, high impact block copolymer polypropylene, elastomer toughening agent, anti-scratch additive, compatibilizer, stabilizer and other additives according to the above weight percentages and mix them evenly;
[0018] (2) The PP raw materials mixed as described above are placed in the main feeding bin of a co-rotating twin-screw extruder, added to the extruder through the feeding screw, and the filler is mixed evenly and then added to the twin-screw extruder from the side feeding port. After melt extrusion, the PP raw materials are cooled and granulated. The process is as follows: the temperature of the first zone is 60-190°C, the temperature of the second to eighth zones is 190-220°C, and the extrusion temperature is 210±10°C; the main screw speed is 550-600r / min, and the water tank temperature is 30°C-60°C. After melt extrusion, cooling, granulation, and drying, a polypropylene composite material with anti-tiger pattern, low shrinkage, and low odor is obtained.
[0019] The advantages of the present invention are:
[0020] (1) Compared with the conventional tiger skin pattern optimization scheme, the present invention can not only solve the tiger skin pattern problem of the workpiece after increasing the melt flow rate of the material, but also ensure the toughness of the material;
[0021] (2) Compared with traditional talcum powder filling materials, fibrous materials have a certain aspect ratio and a large interface bonding area with polypropylene materials, which can orient the polypropylene segments in the direction of the long diameter, thereby reducing the shrinkage of polypropylene materials to a greater extent and improving dimensional stability. In addition, compared with talcum powder, special mineral filling has a lower density. Under the same filling ratio, the density of the composite material will also be lower, which plays a role in lightweighting when applied to interior products.
[0022] (3) The use of odor neutralizers to improve the emission of composite materials can improve the odor of the finished product and reduce the post-processing time, while reducing the residual harmful volatile substances. DETAILED DESCRIPTION
[0023] The following is a further detailed description of the embodiments of the present invention by way of examples and comparative examples, but the present invention is not limited to the scope of the embodiments.
[0024] In the composite material formulations of the comparative example and the embodiment, the melt flow rates of the copolymerized polypropylene used are about 60 g / 10 min and 100 g / 10 min, respectively, and the melt flow rate of the high impact block copolymerized polypropylene is about 40 g / 10 min. The elastomer toughening agents used are POE 7467 and POE C13060D, respectively, with melt flow rates of about 1 g / 10 min and 13 g / 10 min, respectively. The fillers used are 10000 mesh talc and microscopic fibrous special minerals.
[0025] The compatibilizer used is polypropylene grafted maleic anhydride. The odor neutralizer used is a plastic deodorizer, and the anti-scratch additive used is a commercially available amide scratch additive. The stabilizers used are provided by British ICE Company and Ciba Company, and are Negonox DSTP (chemical name: stearyl thiodipropionate), Irganox1010 (chemical name: pentaerythritol tetrakis (3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) and Irgafos 168 (chemical name: tris (2,4-di-tert-butylphenyl) phosphite). Other additives used mainly refer to color components, light stabilizers, etc.
[0026] Example 1
[0027] 59% of copolymerized polypropylene 1, 14% of talcum powder, 9% of POE 1, 10% of POE2, and 2% of other additives and color powder packages are weighed by weight, placed in a high-speed mixer and mixed evenly, and then added from the main feeding port of a twin-screw extruder; 14% of talcum powder and 6% of special minerals are mixed evenly and added from the side feeding port of the twin-screw extruder; after melt extrusion, the mixture is cooled and granulated to prepare a tiger-skin-resistant, low-shrinkage, and low-odor polypropylene composite material. The process is as follows: the temperature of zone 1 is 60-190°C, the temperature of zones 2-8 is 190-220°C, and the extrusion temperature is 210±10°C; the main screw speed is 550-600r / min, and the water tank temperature is 30°C-60°C.
[0028] Example 2
[0029] 10% of copolymer polypropylene 1, 31% of copolymer polypropylene 2, 25% of high-impact block copolymer polypropylene, 12% of POE 2, and 2% of other additives and color powder packages are weighed by weight, placed in a high-speed mixer and mixed evenly, and then added from the main feeding port of a twin-screw extruder, 20% of talcum powder is added from the side feeding port of the twin-screw extruder, and after melt extrusion, the mixture is cooled and granulated to prepare a polypropylene composite material with anti-tiger pattern, low shrinkage, and low odor. The process is as follows: the temperature of zone 1 is 60-190°C, the temperature of zones 2-8 is 190-220°C, and the extrusion temperature is 210±10°C; the main screw speed is 550-600r / min, and the water tank temperature is 30°C-60°C.
[0030] Example 3
[0031] 10% of copolymer polypropylene 1, 30% of copolymer polypropylene 2, 25% of high-impact block copolymer polypropylene, 12% of POE 2, 0.5% of odor neutralizer, 2% of other additives and color powder package are weighed by weight percentage, placed in a high-speed mixer and mixed evenly, and then added from the main feeding port of a twin-screw extruder, 20% of talcum powder is added from the side feeding port of the twin-screw extruder, and after melt extrusion, the mixture is cooled and granulated to prepare a polypropylene composite material with anti-tiger pattern, low shrinkage and low odor. The process is as follows: the temperature of zone 1 is 60-190°C, the temperature of zones 2-8 is 190-220°C, the extrusion temperature is 210±10°C, the main screw speed is 550-600r / min, and the water tank temperature is 30°C-60°C.
[0032] Example 4
[0033] 10% of copolymer polypropylene 1, 31% of copolymer polypropylene 2, 25% of high-impact block copolymer polypropylene, 12% of POE 2, 0.5% of odor neutralizer, 2% of other additives and color powder package are weighed by weight percentage, placed in a high-speed mixer and mixed evenly, and then added from the main feeding port of a twin-screw extruder; 17% of talcum powder and 3% of special minerals are mixed evenly and added from the side feeding port of the twin-screw extruder; after melt extrusion, the mixture is cooled and granulated to prepare a tiger-skin-resistant, low-shrinkage and low-odor polypropylene composite material, and the process is as follows: the temperature of zone 1 is 60-190°C, the temperature of zones 2-8 is 190-220°C, and the extrusion temperature is 210±10°C; the main screw speed is 550-600r / min, and the water tank temperature is 30°C-60°C.
[0034] Example 5
[0035] 10% of copolymer polypropylene 1, 31% of copolymer polypropylene 2, 25% of high-impact block copolymer polypropylene, 12% of POE 2, and 2% of other additives and color powder packages are weighed by weight, placed in a high-speed mixer and mixed evenly, and then added from the main feeding port of a twin-screw extruder; 14% of talcum powder and 6% of special minerals are mixed evenly and added from the side feeding port of the twin-screw extruder; after melt extrusion, the mixture is cooled and granulated to prepare a polypropylene composite material with anti-tiger pattern, low shrinkage and low odor. The process is as follows: the temperature of zone 1 is 60-190°C, the temperature of zones 2-8 is 190-220°C, and the extrusion temperature is 210±10°C; the main screw speed is 550-600r / min, and the water tank temperature is 30°C-60°C.
[0036] Comparative Example 1
[0037] 59% of copolymerized polypropylene 2, 19% of POE 1, and 2% of other additives and color powder packages are weighed by weight, placed in a high-speed mixer and mixed evenly, and then added from the main feeding port of a twin-screw extruder. 20% of talcum powder is added from the side feeding port of the twin-screw extruder. After melt extrusion, the mixture is cooled and granulated to prepare a PP composite material. The process is as follows: temperature of zone 1 is 60-190°C, temperature of zones 2-8 is 190-220°C, extrusion temperature is 210±10°C; main screw speed is 550-600r / min, and water tank temperature is 30°C-60°C.
[0038] Comparative Example 2
[0039] 59% of copolymerized polypropylene 1, 19% of POE 1, 2% of other additives and color powder packages are weighed by weight, placed in a high-speed mixer and mixed evenly, and then added from the main feeding port of a twin-screw extruder. 20% of talcum powder is added from the side feeding port of the twin-screw extruder. After melt extrusion, the mixture is cooled and granulated to prepare a PP composite material. The process is as follows: temperature of zone 1 is 60-190°C, temperature of zones 2-8 is 190-220°C, extrusion temperature is 210±10°C; main screw speed is 550-600r / min, and water tank temperature is 30°C-60°C.
[0040] Comparative Example 3
[0041] 59% of copolymerized polypropylene 1, 9% of POE 1, 10% of POE 2, and 2% of other additives and color powder packages are weighed by weight, placed in a high-speed mixer and mixed evenly, and then added from the main feeding port of a twin-screw extruder, 20% of talcum powder is added from the side feeding port of the twin-screw extruder, and after melt extrusion, the mixture is cooled and granulated to prepare a PP composite material. The process is as follows: temperature of zone 1 is 60-190°C, temperature of zones 2-8 is 190-220°C, extrusion temperature is 210±10°C; main screw speed is 550-600r / min, and water tank temperature is 30°C-60°C.
[0042] Performance evaluation method and implementation standards:
[0043] The material particles prepared by the above method were placed in a 90° C. forced air oven to dry for 2-3 hours, and then the dried particles were injection molded into standard specimens and leather grain plates, and performance tests were performed.
[0044] Performance evaluation method: The tensile performance test is carried out according to GB / T 1040.2 standard, the test speed is 50mm / min, and the sample size is 170mm×10mm×4mm; the bending performance test is carried out according to GB / T 9341 standard, the test speed is 2mm / min, the span is 64mm, and the sample size is 80mm×10mm×4mm; the cantilever beam notch impact test is carried out according to GB / T 1843 standard, the sample size is 80mm×10mm×4mm, the notch retention width is 8.0±0.2mm, and the notch type is A type; the odor test is carried out according to VDA270 standard; the shrinkage rate is tested according to the Pritt method; the tiger skin pattern is evaluated according to the Pritt "mosquito coil".
[0045] The formulas (weight percentage) of the comparative examples and embodiments of the present invention are shown in Table 1, and the corresponding performance test results are shown in Table 2.
[0046] Table 1 Material composition of Examples 1-5 and Comparative Examples 1-3
[0047]
[0048] Table 2 Performance test results of Examples 1-5 and Comparative Examples 1-3
[0049]
[0050]
[0051] From Examples 1-5 and Comparative Examples 1-3 in Table 2, it can be seen that after increasing the melt flow rate, the notched impact is slightly reduced, which is beneficial to increase the tiger stripe distance, that is, effectively improve the tiger stripe of the material. In addition, after a part of the talc is replaced by a special mineral, the toughness of the material can be effectively improved, and the effect on the tiger stripe is small. The toughening effect of replacing part of POE with high-impact block copolymer polypropylene, when the melt flow rate and notched impact strength are similar, the composite material of the high-impact block copolymer polypropylene system has a better effect on improving the tiger stripe.
[0052] From Examples 1-5 and Comparative Example 2, it can be seen that after adding special minerals, the density and shrinkage of the material are significantly reduced. As the proportion of special minerals increases, the density and shrinkage decrease more and more, indicating that special minerals have further restrictions on the crystallization of PP compared to talcum powder, and the lightweight effect is significant. From Example 1 and Comparative Examples 1-2, it can be seen that under the same process, the melt flow rate of the material is increased.
[0053] , will slightly increase the shrinkage of the material. After adding special minerals, it can weaken the effect of increasing the melt flow rate on the shrinkage, while reducing the density of the material, which is beneficial to dimensional stability.
[0054] It can be seen from Examples 2-5 that the odor neutralizer has some influence on the toughness of the composite material, resulting in a decrease in notched impact strength, but the odor neutralizer can effectively reduce the odor level of the composite material to level 3.0.
[0055] The above is only a specific embodiment of the present invention, which is to illustrate the technical concept and features of the present invention, and is intended to enable those skilled in the art to understand the ideas and contents of the present invention. Therefore, all those defined by the claims should be included in the protection scope of the present invention.
Claims
1. An anti-tiger pattern, low shrinkage, low odor polypropylene composite material, characterized by: The invention is composed of the following raw materials in weight percentage: copolymerized polypropylene: 30-60%; high impact block copolymerized polypropylene: 0-30%; Elastomer toughening agent: 0-20%; Filler: 15-25%; Compatibility agent: 0-3%; Odor neutralizer: 0-3%; Anti-scratch additive: 0.2-2%; Stabilizer: 0.1-2%; other additives: 0-5%.
2. The anti-tiger grain, low shrinkage, low odor polypropylene composite material according to claim 1, characterized in that: The melt flow rate of the copolymerized polypropylene is 30-100 g / 10 min, and it has an anti-tiger pattern effect; the melt flow rate of the high-impact block copolymerized polypropylene is 10-50 g / 10 min.
3. The anti-tiger grain, low shrinkage, low odor polypropylene composite material according to claim 1, characterized in that: The elastomer toughening agent is ethylene-octene copolymer or styrene-ethylene-butadiene-styrene block copolymer or a combination of the two, with a density of 0.88-0.91 g / cm3 and a melt flow rate of 1-15 g / 10 min.
4. The anti-tiger grain, low shrinkage, low odor polypropylene composite material according to claim 1, characterized in that: The filler is one or more of talcum powder, whisker, basalt fiber, glass fiber and carbon fiber.
5. The anti-tiger grain, low shrinkage, low odor polypropylene composite material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene, the effective grafting activity is above 5%, and the melt index is 5-20g / 10min.
6. The anti-tiger grain, low shrinkage, low odor polypropylene composite material according to claim 1, characterized in that: The odor neutralizer is one or more of a plastic deodorizer, an adsorbent, a natural zeolite, and an extractant.
7. The anti-tiger grain, low shrinkage, low odor polypropylene composite material according to claim 1, characterized in that: The anti-scratch additive is one or more of an amide additive or a silicone additive.
8. The anti-tiger grain, low shrinkage, low odor polypropylene composite material according to claim 1, characterized in that: The stabilizer is a primary antioxidant and a secondary antioxidant that are considered necessary by those skilled in the art, wherein the primary antioxidant is a hindered phenol or thioester antioxidant, and the secondary antioxidant is a phosphite or lipid antioxidant.
9. The anti-tiger grain, low shrinkage, low odor polypropylene composite material according to claim 1, characterized in that: The other additives are one or a combination of anti-light additives, flame retardants, antistatic additives, surfactants, plasticizers, and antimicrobial additives that are considered necessary by those skilled in the art.
10. The method for preparing the anti-tiger grain, low shrinkage, low odor polypropylene composite material according to any one of claims 1 to 9, characterized in that: The specific steps are as follows: (1) Weigh copolymer polypropylene, high impact block copolymer polypropylene, elastomer toughening agent, anti-scratch additive, compatibilizer, stabilizer and other additives according to the above weight percentages and mix them evenly; (2) The mixed polypropylene raw material is placed in the main feeding bin of a co-rotating twin-screw extruder, added to the extruder through the feeding screw, the filler is mixed evenly, and then added to the twin-screw extruder from the side feeding port, and cooled and granulated after melt extrusion. The process is as follows: the temperature of the first zone is 60-190°C, the temperature of the second to eighth zones is 190-220°C, the extrusion temperature is 210±10°C; the main screw speed is 550-600r / min, and the water tank temperature is 30°C-60°C. After melt extrusion, cooling, granulation, and drying, an anti-tiger pattern, low shrinkage, and low odor polypropylene composite material is obtained.
Citation Information
Patent Citations
Low-density high-performance polypropylene composite material capable of being used for thin-wall injection molded part and preparation method thereof
CN106751353A
Thermal-deformation-resistant, low-thermal-shrinkage and impact-resistant polypropylene composite material and preparation method thereof
CN112662113A
Scratch-resistant, low-thermal-conductivity and light-weight polypropylene composite material and preparation method thereof
CN117866338A
Low-odor, high-toughness and high-rigidity modified polypropylene material and preparation method thereof
CN117866372A